Dynamic nature of somatic chromosomal mosaicism, genetic-environmental interactions and therapeutic opportunities in disease and aging - Vorsanova, Svetlana G. (Mol Cytogenet, 2020)
BACKGROUND: Somatic chromosomal mosaicism is the presence of cell populations differing with respect to the chromosome complements (e.g. normal and abnormal) in an individual. Chromosomal mosaicism is associated with a wide spectrum of disease conditions and aging. Studying somatic genome variations has indicated that amounts of chromosomally abnormal cells are likely to be unstable. As a result, dynamic changes of mosaicism rates occur through ontogeny. Additionally, a correlation between disease severity and mosaicism rates appears to exist. High mosaicism rates are usually associated with severe disease phenotypes, whereas low-level mosaicism is generally observed in milder disease phenotypes or in presumably unaffected individuals. Here, we hypothesize that dynamic nature of somatic chromosomal mosaicism may result from genetic-environmental interactions creating therapeutic opportunities in the associated diseases and aging. CONCLUSION: Genetic-environmental interactions seem to contribute to the dynamic nature of somatic mosaicism. Accordingly, an external influence on cellular populations may shift the ratio of karyotypically normal and abnormal cells in favor of an increase in the amount of cells without chromosome rearrangements. Taking into account the role of somatic chromosomal mosaicism in health and disease, we have hypothesized that artificial changing of somatic mosaicism rates may be beneficial in individuals suffering from the associated diseases and/or behavioral or reproductive problems. In addition, such therapeutic procedures might be useful for anti-aging strategies (i.e. possible rejuvenation through a decrease in levels of chromosomal mosaicism) increasing the lifespan. Finally, the hypothesis appears to be applicable to any type of somatic mosacism.